Moleculobiological characteristics of oral squamous cell carcinomas - Tanić Nikola; Dedović-Tanić Nasta; Popović Brandon; Kosanović Rade; Milašin Jelena (Serbian Medical Society - Dental Section, Belgrade, 2011)
Oral squamous cell carcinomas (OSCCs) are associated with poor prognosis, and despite advances in therapy approaches, no major improvement in survival has been achieved in the recent years. Efforts are now directed toward finding new biological markers that could predict tumor behavior more accurately. OSCCs, as the majority of malignant tumors, arise from progressive accumulation of genetic and epigenetic lesions, transforming normal cells into malignant. In this paper, an analysis of current studies directed to understanding the underlying mechanisms of OSCC pathogenesis was presented. The emphasis was put on mutational analysis of cancer genes, as well as on the role of viral infections and methylation processes in OSCC. Finally, an overview of studies that tried to determine the possibility for developing OSCC was given.